Quantification of Wettability and Surface Tension of Liquid Aluminum 7075 Alloy on Various Substrates - Chukwudalu Uchenna Uba; Jonathan Richard Raush (Journal of Manufacturing and Materials Processing)
To support computational studies and process optimization that require temperature-dependent thermophysical properties, this study characterized the wettability, surface tension, liquid–solid interfacial tension (IFT), and work of adhesion of Al 7075-T6 alloy from 923–1073 K under argon on porous alumina, tungsten, and nonporous alumina substrates using sessile drop experiments and Young’s and Young–Dupre equations, respectively. Furthermore, the substrates’ room-temperature surface free energy (SFE) characteristics were characterized using the Owens–Wendt–Rabel–Kaelble model. The contact angle results revealed the alloy’s poor wettability on all substrates. The surface tension data ranged from 718.87–942.90 mN·m−1 in decreasing order of tungsten, porous alumina, and nonporous alumina. The SFE results of the porous alumina, nonporous alumina, and tungsten substrates were 44.92, 43.32, and 42.03 mN·m−1, respectively. Also, the calculated liquid–solid IFT values ranged from 539.24–835.51 mN·m−1 in decreasing order of porous alumina, tungsten, and nonporous alumina. Additionally, the calculated work of adhesion values ranged from 123.97–479.44 mN·m−1 in decreasing order of nonporous alumina, tungsten, and porous alumina, respectively. Thus, the wettability, surface tension, and liquid–solid IFT of Al 7075-T6 alloy on the substrates were affected by the substrates’ SFE characteristics, thereby affecting the work of adhesion.